“Analisa Dissenting Opinion Dalam Hasil Putusan Permohonan Perkara Nomor 35/PUU/XXII/2024 Terhadap Pasal 35 Ayat 1 UU No 13 Tahun 2023 Tentang Ketenagakerjaan - Ohandi, Max Andrew; Syam, Radian (Neolectura, 2025)
This research highlights Judge Guntur Hamzah's dissenting opinion in the Constitutional Court's decision regarding Article 35 paragraph (1) of Law no. 13 of 2023 concerning Employment. He criticized the phrase